Evidence for Viral Interference and Cross-reactive Protective Immunity Between Influenza B Virus Lineages. (6th January 2018) - Laurie, Karen L; Horman, William; Carolan, Louise A; Chan, Kok Fei; Layton, Daniel; Bean, Andrew; Vijaykrishna, Dhanasekaran; Reading, Patrick C; McCaw, James M; Barr, Ian G
Abstract : Using a ferret model of human influenza, we demonstrate that infection with one influenza B virus can prevent or limit infection with an influenza B virus of the other lineage. This occurs when infections are separated by days or weeks. Abstract: Background: Two influenza B virus lineages, B/Victoria and B/Yamagata, cocirculate in the human population. While the lineages are serologically distinct, cross-reactive responses to both lineages have been detected. Viral interference describes the situation whereby infection with one virus limits infection and replication of a second virus. We investigated the potential for viral interference between the influenza B virus lineages. Methods: Ferrets were infected and then challenged 3, 10, or 28 days later with pairs of influenza B/Victoria and B/Yamagata viruses. Results: Viral interference occurred at challenge intervals of 3 and 10 days and occasionally at 28 days. At the longer interval, shedding of challenge virus was reduced, and this correlated with cross-reactive interferon γ responses from lymph nodes from virus-infected animals. Viruses from both lineages could prevent or significantly limit subsequent infection with a virus from the other lineage. Coinfections were rare, indicating the potential for reassortment between lineages is limited. Conclusions: These data suggest that innate and cross-reactive immunity mediate viral interference and that this may contribute to the dominance of a specific influenza B virus lineage in any given influenza season. Furthermore, infection with one influenza B virus lineage may be beneficial in protecting against subsequent infection with either influenza B virus lineage.